Venous thromboembolism in menopausal period – part III - Stefańczyk, Ludomir; Górski, Aleksander; Gajewicz, Witold; Grzelak, Piotr; Stachowiak, Grzegorz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2005)
In the second part of our paper sonographic diagnostics of thromboembolic disease was presented ( Przegląd Menopauzalny 2004; 6: 51-54). In the third part issues concerned with acute phase of thrombosis and its the most dangerous complication - pulmonary embolism are raised. Pharmacotherapy standards based on low-molecular-weight heparin use and experiences concerned with thrombolytic therapy of massive pulmonary embolism were presented. There are also informations about temporary inferior vena cava filters implantation. Changes in thromboembolic disease therapeutic guidelines during last years were also presented.